Daugiaskiemenių vardažodžių kilnojamosios kirčiavimo paradigmos raida lietuvių kalboje - Stundžia, Bonifacas (Baltistica, 2010)
DEVELOPMENT OF THE MOBILE ACCENT PARADIGM IN LITHUANIAN POLYSYLLABIC NOMINALSThe traditional mobile accent paradigm, alternating stress between the last and the initial syllables in polysyllabic words, has developed into two types of neomobility in certain classes of appellatives and nomina propria in Lithuanian. Different character of stress alternation is a distinctive feature of the two neomobile accent types.The first type of neomobility is characterized by the alternation of stress between the last and the penultimate syllables of polysyllabic words, while the second type of neomobility is typical of tetrasyllabic nominals alternating stress between the last and the antepenultimate syllables.The first type of neomobility‚ which seems to have originated directly from Saussure’s Law, has spread (a) to adjectives (almost exclusively u-stem ones), (b) to some numerals, (c) to toponyms, and (d) to forms of the so-called collective plural, mostly derived from anthroponyms. The majority (4/5) of toponyms in question belongs to the class of pluralia tantum in -(i)ónys (accent paradigm 3) and -(i)aĩ (accent paradigm 4), while rare cases of singularia tantum toponyms end in -(i)a.The 3rd accent paradigm of polysyllabic toponyms could be interpreted in many cases as a relic, reflecting changes in the accentuation of derivatives triggered by Saussure’s Law. Meanwhile, the 4th accent paradigm seems to be inherited from the so-called collective plural (pluralia tantum toponyms) or to have arisen because of the replacement of acute under circumflex metatony, influence of palatal consonants, etc. (singularia tantum toponyms).The second type of accentual neomobility seems to be later than the first one. It has spread mostly to tetrasyllabic compounds with the composition vowel -a- or disyllabic first member. It seems to have originated from the tendency of shifting stress from the initial to the adjacent syllable, which represents either the composition vowel -a- or the syllable preceding the zero juncture of a fixed stress compound.
Keywords: akcentologija; neomobilumas; lietuvių kalba; akcentinė paradigma; kilnojamoji kirčiavimo paradigma